United Arab Emirates : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation highlights that the economic recovery in the United Arab Emirates is continuing despite the uncertain global economic environment. The banking sector has remained well capitalized and profitable, despite a continued rise in nonperforming loans and higher provisioning. Executive Directors have welcomed the continued economic recovery and favorable near-term outlook, but noted downside risks from the uncertain global environment. Directors have encouraged the authorities to continue their efforts to sustain growth and diversify the economy, while maintaining macroeconomic and financial stability.